La relación accionista-empresa en internet: análisis desde el enfoque de confianza - Alonso Almeida, María del Mar (2008)
During the last decade there has been a break of trust of the shareholders to the company. Several factors converge to bring this breakthrough on the one hand, certain abuses of the “creative” reflected in an excessive “make-up” of the financial information and on the other hand, poor practices among some market players that have resulted in distrust and uncertainty about the present and the prospects for future. The aim of this paper is analyze trust between shareholders and companies and provide a model of communication via Internet to contribute to build confidence between them.